Alumni survey of Masters of Public Health (MPH) training at the Hanoi School of Public Health - Nguyen Ha; Bui Quyen; Le Linh; Rotem Arie (BMC, 2007)
Abstract Background 1) To elicit the opinions of the Public Health alumni of the MPH program; 2) To assess the applicability of the knowledge and skills acquired; 3) To identify the frequency of the public health competencies that the alumni performed. Methods We requested 187 graduates to complete a self-administered questionnaire and conducted in-depth interviews with 8 alumni as well as a focus group discussion with 14 alumni. Results In total 79.1% (148) of the MPH graduates completed and returned the questionnaire. Most alumni (91%) agreed that the MPH curriculum corresponded with the working requirements of public health professionals; and nearly all were satisfied with what they have learnt (96%). Most respondents said that the MPH program enabled them to develop relevant professional skills (95%) and that they were satisfied with the curriculum (90%). Notably fewer respondents (73%) felt that the MPH program structure was balanced and well designed. Most alumni (64.3%) were satisfied with Hanoi School of Public Health (HSPH) full-time lecturers; but even more (83%) were satisfied with visiting lecturers. The most commonly selected of the 34 pre-identified public health competencies were: applying computer skills (66.4%), planning and managing health programs (47.9%), communicating with the community and/or mobilizing the community to participate in health care (43.2%). Overall, the MPH alumni felt that HSPH emphasized research methods at the expense of some management and operational competencies. The most important challenges at work identified by the alumni were insufficient skills in: data analysis, decision making, inter-sectoral cooperation development, English language and training. Conclusion The training program should be reviewed and revised to meet the needs of its graduates who enter diverse situations and positions. English language skills were identified as top priority for further emphasis. The training program should comply with a more advanced accreditation system and standards.